Toward a Healthy and Harmonious Life in China : Stemming the Rising Tide of Non-Communicable Diseases - World Bank (Washington, DC, 2017)
China's 12th five-year plan (2011-2015) aims to promote inclusive, equitable growth and development by placing an increased emphasis on human development. Good health is an important component of human development, not only because it makes people's lives better, but also because having a healthy and long life enhances their ability to learn, acquire skills, and contributes to society. Indeed, good health is a fundamental right of every human being. Good health among a population can also enhance economic performance by improving labor productivity and reducing economic losses that arise from illnesses. The findings and recommendations can inform and promote a broad dialogue toward the development of a multisectoral response to effectively address the growing burden of Non Communicable Diseases (NCDs), including a better alignment of the health system with the population's health needs. The report also advocates implementing 'health in all' policies and actions for a multisectoral response to NCDs in China to help achieve the ultimate goal of 'harmonious' development and growth.